Desenvolvimento de compósitos de nanotubos de carbono com matrizes metálicas de alumínio e a liga AA7050 - Luana Araújo Batista (2022)
The very high yield stress of carbon nanotubes (CNTs), associated with other properties such as high thermal and electrical conductivity and low coefficient of thermal expansion, makes it excellent candidates for reinforcing ductile matrices. Aluminum composites with CNTs have been developed to obtain composites with low specific weight and high mechanical strength. The main objective of this doctoral thesis is to evaluate the feasibility of using CNTs in Al-based metal matrix composites and their respective consolidation. For this, three different composites were produced with the CNTs: (i) commercially pure aluminum, (ii) with the AA7050 alloy, and (iii) a hybrid composite joining the three materials. The CNTs were dispersed and impregnated in the metallic powders by ultrasound techniques and by a very high energy ball mill. Powder metallurgy consolidation involved hot pressing and extrusion. The impact of different processes on the composite quality and the structural integrity of the CNTs was evaluated throughout the work. For characterization, scanning electron microscopy, x-ray diffraction, Raman spectroscopy, atomic force spectroscopy, thermography, x-ray fluorescence, microhardness, and abrasion wear were used. It was verified that CNTs can reinforce both matrices as long as they are dispersed, well adhered, and with their structural integrity preserved. The technique that generated the best result was the production of the composite by ultrasound with a retroevaporator. Al composites verified that there is a maximum content of CNTs that can be incorporated without large damage to the mechanical conformation. Since the increase in the concentration of CNTs, the difficulty in consolidating the composite grows, resulting in its weakening. In general, the use of CNTs as reinforcement increases the hardness and abrasive wear resistance of the samples. For example, in 0.25 wt% CNT/Al composite occurred a 50% reduction in mass loss. For the 0.5 wt% CNT/AA7050 composite there was an increase in hardness of 18.5% after alloy aging process.